The impact of risk and time preferences on smoking behaviour in the context of a contingency management programme - Carnegie, Tyryn (School of Economics, 2021)
While there is an established body of research examining risk preferences, time preferences and smoking behaviour, there is little literature exploring the relationship between risk preferences, time preferences, and smoking cessation contingency management (CM) programmes. This dissertation evaluates a CM study and its effect on smokers' ability to quit and smoking intensity, together with their risk and time preferences. The experiment comprises 87 University of Cape Town students wanting to quit smoking, randomly assigned into treatment and control groups. Risk and time preferences are elicited at the beginning of the programme, using incentive-compatible decision-making tasks. The relationship between the individuals' risk preferences, time preferences, and smoking outcomes is explored using two general approaches: standard statistical models and structural models. In the structural models, maximum likelihood estimation is used to estimate time preference parameters jointly with risk preference parameters. Results are broadly consistent across the two approaches. With respect to abstinence, the statistical model suggests that the likelihood of abstinence increases with discount rates, while the structural models suggest CM reduces the effect that time preferences have on abstinence. Neither approach finds a difference in risk preferences between abstinent and non-abstinent participants. In terms of smoking intensity, both approaches unexpectedly find smoking intensity to increase with risk aversion, and neither approach finds a relationship between smoking intensity and time preferences.